An assessment of the impact of make up in film productions: my experiences during work related learning from February 2016 to November 2016 - Mnkandla, Thabisile (Midlands State University, 2018)
The study exposes the challenges which are being faced after the implementation of debt cancellation in Mutare. The research was conducted in Mutare urban with the aim of assessing how debt cancellation has contributed in the fall of service delivery. The objective of this study is to examine the effects of debt cancellation on service delivery in Mutare and coming up with strategies in order to cope up against the effects of debt cancellation. As a way of fulfilling this, questionnaires, interviews and focus group discussions were implemented for the researcher to have data on his study. The researcher founded out that the cancellation of debts resulted in MCC suffering from liquidity crisis and this heavily affected service delivery as the council neglected some of the services it offered to the residents all because of funds being unavailable to ignite service delivery.